Car drivers’ characteristics and the maximum walking distance between parking facility and final destination - van der waerden, Petrus; Timmermans, Harry; de Bruin-Verhoeven, Marloes (Journal of Transport and Land Use, 2015)
In this paper the relationship between car drivers’ personal and trip characteristics and the maximum distance car drivers are willing to walk between a parking facility and the final destination(s) will be discussed. The willingness to walk is investigated in the context of four different trip purposes: weekly shopping, non-weekly shopping, work, and social activities. The analyses are based on responses of almost 340 members of the Eindhoven University of Technology’s University Parking Panel. The questions regarding car drivers’ willingness to walk were included in an Internet-based questionnaire that was distributed in 2011. It appears that car drivers are willing to walk short distances in the case of weekly shopping and work. Longer walking distances are accepted in the case of non-weekly shopping. The influence of car drivers’ personal and trip characteristics was investigated using multinomial regression analysis. This analysis shows that the most influential characteristics are the trip-related characteristics “frequency of car use” and “visit duration.” The parameter estimates show that in the case of weekly and non-weekly shopping, the more the car is used and the longer car drivers stay at a destination, the higher the probabilities of longer-distance categories. For the trip purposes work and leisure, the opposite holds true.